Rewiring AMPK and Mitochondrial Retrograde Signaling for Metabolic Control of Aging and Histone Acetylation in Respiratory-Defective Cells - R. Magnus N. Friis; John Paul Glaves; Tao Huan; Liang Li; Brian D. Sykes; Michael C. Schultz (Cell Reports, 2014)
Summary: Abnormal respiratory metabolism plays a role in numerous human disorders. We find that regulation of overall histone acetylation is perturbed in respiratory-incompetent (ρ0) yeast. Because histone acetylation is highly sensitive to acetyl-coenzyme A (acetyl-CoA) availability, we sought interventions that suppress this ρ0 phenotype through reprogramming metabolism. Nutritional intervention studies led to the discovery that genetic coactivation of the mitochondrion-to-nucleus retrograde (RTG) response and the AMPK (Snf1) pathway prevents abnormal histone deacetylation in ρ0 cells. Metabolic profiling of signaling mutants uncovered links between chromatin-dependent phenotypes of ρ0 cells and metabolism of ATP, acetyl-CoA, glutathione, branched-chain amino acids, and the storage carbohydrate trehalose. Importantly, RTG/AMPK activation reprograms energy metabolism to increase the supply of acetyl-CoA to lysine acetyltransferases and extend the chronological lifespan of ρ0 cells. Our results strengthen the framework for rational design of nutrient supplementation schemes and drug-discovery initiatives aimed at mimicking the therapeutic benefits of dietary interventions. : Perturbation of respiratory function plays a role in numerous disease states. Here, Friis et al. demonstrate that ρ0 yeast, which have lost their mitochondrial genome, display defective maintenance of histone acetylation. They show that this defect can be ameliorated through dual activation of the AMPK homolog Snf1 and the retrograde response pathway. This genetic manipulation allows for accumulation of the storage carbohydrate trehalose and maintenance of the supply of acetyl-CoA and prolongs the viability of ρ0 cells during chronological aging.